Transitional Antibiotic Therapy - Richard Quintiliani; Helen M Crowe; Charles Nightingale (Canadian Journal of Infectious Diseases)
With all the fiscal restraints in healthcare systems. it is crucial to develop methods to treat infections that are both clinically sound and cost-effective. Of the various options available. the rapid transition from intravenous to oral therapy represents one of the most effective ways to attain these goals. Moreover, it has the further advantages of shortening hospital stay, reducing nosocomial bacteremia and avoiding the need to rely upon intravenous technicians and equipment. Although there is a need for more patient outcome studies with this approach, the early experience with transitional therapy appears promising.